Investigation of numerical solution approaches for the cavitating flow analysis of twisted hydrofoils - Oksuz, Sinem; Usta, Onur; Celik, Fahri (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
In this study, geometrical parameters such as twist, section thickness, and angle of attack are numerically investigated for their influence on lift and drag coefficients, as well as cavitation development. The Delft 11 Hydrofoil, a twisted version of the NACA0009 foil with a -2 degrees angle of attack, is used as the benchmark geometry for validation studies under both non-cavitating and cavitating flow conditions. After the validation studies, the geometries of the NACA0009 and NACA0015 hydrofoils were redesigned as half-twisted and twisted. These redesigned hydrofoils, along with the original no-twist versions, were analyzed under cavitating flow conditions within an angle of attack range of -2<5 degrees. In the study, three-dimensional, unsteady, cavitating flow is modelled by two different solution approaches, RANS and DES, with the SST Menter k-omega turbulence model. The Schnerr-Sauer cavitation model is employed to obtain cavitation formation. The same physical conditions with RANS simulations are performed using a refined mesh with the DES method, focusing particularly on accurately and precisely obtaining cavitation development, especially cavitation cycles. Additionally, DES analyses were performed for various time step values, demonstrating the specific influence of the time step on cavitation cycles. The results show that while the RANS method effectively predicts the lift and drag forces of the hydrofoil, the DES method is crucial for capturing cavitation dynamics with greater precision, particularly for obtaining cavitation cycles. The results also indicate that twisted hydrofoil geometries produce more lift and drag force than half-twisted and no-twist geometries for both NACA0009 and NACA0015 hydrofoils. In addition, the cavitation formation around the hydrofoil generally increases with the twistiness.
Keywords: Twisted hydrofoil; Cavitation development; Cavitation cycle; Delft 11 hydrofoil; NACA0009 and NACA0015; RANS; DES; LARGE-EDDY SIMULATION; LES; Engineering; Oceanography